Localization of the Mandibular Canal in a Turkish Population: a Retrospective Cone-Beam Computed Tomography Study - Fahrettin Kalabalik; Emre Aytuğar (eJournal of Oral Maxillofacial Research, 2019)
Objectives: The aim of this study was to determine the location of the mandibular canal at the mental foramen region that is essential in order to prevent injuries to the inferior alveolar neurovascular bundle during mandibular surgical procedures.